Relationship Between Daily Living Activity And Self Dependency In Non-Hemoragic Stroke Patients In The Stroke Unit - Fitriani, Indah Nur; Soesanto, Edy; Indanah, Indanah (Pusat Penelitian dan Pengabdian Masyarakat STIKES Banyuwangi, 2025)
Stroke is a chronic disease that affects the quality of life and ability of daily living activities (ADL) of patients, especially in ischemic stroke patients. In Indonesia, stroke is the third largest cause of disability and death, 25.8 percent of sufferers experience total or partial paralysis. This causes sufferers to have difficulty in carrying out daily activities or Activity of daily living (ADL) and independence of self-perception (Self dependency). The purpose of this study was to determine the relationship between Activity Daily Living (ADL) and Self Dependency in non-hemorrhagic stroke patients. This study was conducted in December 2024 in the stroke unit of RSUD dr. Loekmono Hadi Kudus using a descriptive analytical design with a cross-sectional approach. The population in this study was 250 with a sample of 106 patients selected using a purposive sampling technique. Data were collected through a questionnaire that included a measurement instrument for the level of dependence in the form of a questionnaire and a measuring instrument for calculating ADL (Barthel index). Data analysis using the Gamma Correlation test. The results of the analysis using the Gamma Correlation test statistical test with the SPSS program obtained a p-value of 0.001 < (a = 0.05) with a correlation coefficient (0.963) meaning that there is a very strong relationship between daily living activities and independence in non-hemorrhagic stroke patients in the Stroke Unit of Dr. Loekmono Hadi Kudus Hospital. Independence in cases of non-hemorrhagic stroke patients in the Stroke Unit of Dr. Loekmono Hadi Kudus Hospital mostly experienced moderate dependence while patient independence was in the category of requiring severe dependence assistance.